THE EFFECT OF COMMERCIAL FEEDING FREQUENCY ON THE ABSOLUTE LENGTH GROWTH OF 2-3 cm COMET FISH (Carassius auratus) - Usu Rismayanti; Muhajir Muhajir; Indra Wirawan (Universitas Mataram, 2025)
The comet fish (Carassius auratus) is one type of freshwater ornamental fish that has many enthusiasts and maintains a relatively stable price in both domestic and international markets. The high demand for comet fish needs to be supported by excellent feed given to the fish, whether in the form of natural feed or commercial feed. Commercial feed has many advantages, including having a very complete and balanced nutritional composition as well as consistent availability throughout the year. In addition, one of the important elements in feed management is the feeding frequency. Feeding too infrequently can cause the fish to lack nutrients when needed, whereas feeding too often can reduce water quality. This study aims to determine the effect of commercial feed feeding frequency on the absolute length growth of comet fish. This study uses the Complete Randomized Design (CRD) experimental method with 3 treatments and 9 repetitions, where treatment A (frequency 2 times a day), B (frequency 3 times a day), and treatment C (frequency 4 times a day). The test animals were comet fish measuring 2-3 cm, totaling 81 individuals with a stocking density of 1 fish/L. The experimental medium used freshwater with a volume of 3 L per container. The results of the study showed that treatment B provided the best results for the absolute length growth of 2-3 cm comet fish at 2.2 cm per fish. Water quality data showed a water temperature ranging from 28.1 to 28.3 °C, a pH ranging from 7.16 to 7.19, and dissolved oxygen ranging from 5.39 to 5.57 ppm.